Single-phase dual emissive Cu:CdS–ZnSe core–shell nanocrystals with "zero self-absorption" and their application in white light emitting diodes1. Issue 15 (21st April 2015) - Zhang, Zhuolei; Luan, Siyuan; Huang, Keke; Zhang, Ying; Shi, Zhan; Xie, Renguo; Yang, Wensheng
<x xml:space="preserve">Abstract</x> Single phase dual emissive Cu:CdS–ZnSe NCs exhibited flexible two emission bands in the whole visible region. This novel phosphor shows potential for use as color convertors in white light emitting diodes (WLEDs).